2013
DOI: 10.1073/pnas.1301055110
|View full text |Cite
|
Sign up to set email alerts
|

Relation between ordering and shear thinning in colloidal suspensions

Abstract: Colloidal suspensions exhibit shear thinning and shear thickening. The most common interpretation of these phenomena identifies layering of the fluid perpendicular to the shear gradient as the driver for the observed behavior. However, studies of the particle configurations associated with shear thinning and thickening cast doubt on that conclusion and leave unsettled whether these nonequilibrium phenomena are caused primarily by correlated particle motions or by changes in particle packing structure. We repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 39 publications
2
39
1
Order By: Relevance
“…The latter authors investigated a suspension of colloidal spheres which formed aligned string phases during shear, but no significant anisotropy in the viscous response was detected. Also, Stokesian dynamics simulations showed that shear thinning of the viscosity is decoupled from the layering of a stable colloidal suspension under shear [63]. For the flocculated suspensions investigated here, the loss moduli also show a weaker dependence on shear rate, and hence on the structural anisotropy, suggesting that the hydrodynamic contributions to the stress do not depend too strongly on the microstructure.…”
mentioning
confidence: 66%
“…The latter authors investigated a suspension of colloidal spheres which formed aligned string phases during shear, but no significant anisotropy in the viscous response was detected. Also, Stokesian dynamics simulations showed that shear thinning of the viscosity is decoupled from the layering of a stable colloidal suspension under shear [63]. For the flocculated suspensions investigated here, the loss moduli also show a weaker dependence on shear rate, and hence on the structural anisotropy, suggesting that the hydrodynamic contributions to the stress do not depend too strongly on the microstructure.…”
mentioning
confidence: 66%
“…24,43,68 Polydispersed systems can pack more densely because the smaller particles fill the voids between larger ones. 43,56,69,70 Deformability of particles also increases the packing fraction, because particles can squeeze past each other and enhance the effect of shear. 42,56 However, there is no universally accepted way to predict the value of Φ max .…”
Section: Reference Equationmentioning
confidence: 99%
“…There are several issues responsible for such behavior, as pointed out by many researchers in last couple of decades. 61 These explanations suggest that there exists strong particle layering and molecular ordered behavior in case of shear thinning fluid flow. As observed from Fig.…”
Section: Variation Of Average Wall Concentration With Various Opmentioning
confidence: 99%